Hic sita Sigea est: satis hoc: Luisa Sigea and the role of D. Maria, Infanta of Portugal, in female scholarship - Frade, Sofia (2018)
Luisa Sigea is a very unusual example of a female scholar for both Portugal and Spain. Educated by her father, Diego Sigeo, Luisa was particularly famous for knowing Latin, Greek, Hebrew, Chaldean, and Arabic as well as some modern languages. In 1542, she went with her sister to Queen Catarina’s court. Here they were at the service of the king’s sister, D. Maria of Portugal. Luisa had access to the royal library and could dedicate herself to her literary pursuits. Her most famous works, produced during these years, are: Duarum Virginum Colloquium de vita aulica et privata Loysa Sigea Toletana auctore, editum Vlyssiponae, anno salutis MDLII, a bucolic dialogue filled with classical topoi, and Syntra, a poem dedicated to her patron (D. Maria). We also have some letters, including letters sent to Pope Paul III. Sigea was by far the best and most renowned female scholar of her age.